ANALISIS PEMETAAN EMPAT PERGURUAN TINGGI SWASTA BERDASARKAN BRAND EQUITY - Olvia Fitri Dwi Puspita Sari; AMA Suyanto (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2021)
The development of education in Indonesia, which continues to make progress, is evidenced by the growing number of universities and competitors among others. This study aims to map universities with slices of kemenristekdikti, Webometrics, and QS World Star rankings based on brand equity. This research uses quantitative method with a survey to 386 respondents who know the existence of Telkom University, Binus University, Islamic University of Indonesia, and Muhammdiyah University of Yogyakarta who are or have studied higher education. This is a type of descriptive research with multidimensional scalling analysis techniques. The results showed that Telkom University, Binus University, Islamic University of Indonesia, and Muhammadiyah University of Yogyakarta are in the same quadrant with close proximity, meaning that the competition between the four is high. Furthermore, Muhammadiyah University of Yogyakarta has superior value compared to its competitors based on brand equity. Each college continues to increase its brand equity so as to increase its competitive advantage.